2016
DOI: 10.1016/j.clon.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Total Mucosal Irradiation with Intensity-modulated Radiotherapy in Patients with Head and Neck Carcinoma of Unknown Primary: A Pooled Analysis of Two Prospective Studies

Abstract: At a median follow-up of 36.1 months, the use of TM-IMRT was associated with good local control. Toxicity was comparable with previously reported TM-IMRT regimens encompassing similar mucosal volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…IMRT techniques could spare patients from extensive toxicity . A moderate dose, such as 54 Gy, may also be sufficient for mucosal control, but 54Gy dose were delivered to the total mucosal regions for consideration of acute toxicities. This study showed the mucosal control rate of 100% with acceptable toxicities, indicating such approach is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT techniques could spare patients from extensive toxicity . A moderate dose, such as 54 Gy, may also be sufficient for mucosal control, but 54Gy dose were delivered to the total mucosal regions for consideration of acute toxicities. This study showed the mucosal control rate of 100% with acceptable toxicities, indicating such approach is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the low median mucosal recurrence rate following comprehensive radiotherapy of 9.5%, Cuaron et al proposed ongoing consideration of mucosal structure sparing and dose lowering. Moreover, in Richards et al head and neck CUP cohort, all 36 patients were treated with IMRT and received 54 Gy to the mucosa at 1.8 Gy per fraction . They not only reported OS and locoregional control rates similar to other studies that included lower mucosal doses, but also demonstrated rates comparable to studies with higher doses, suggesting that dose reduction does not compromise outcome.…”
Section: Discussionmentioning
confidence: 86%
“…This rate was found to be three times higher (15%) in patients treated with IMRT without laryngeal sparing in Chen et al's study of 51 head and neck CUP patients (53% IMRT, 59% chemotherapy) . Richards et al report a median PEG tube duration of 35 days (range 22‐804 days) for the 28.7% of patients who ultimately required tube placement . Lu et al and Mourad et al found significantly lower rates of stricture in their head and neck CUP cohorts, for which a larynx‐sparing approach was used.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations